COGNITIVE REHABILITATION THERAPY: WHAT IS IT AND WHY ARE WE NOT UTILIZING IT? - Gorman, Jenna (Acta Scientiae et Intellectus, 2024)
Rehabilitation is a medical process that one may go through after a traumatic event, like a stroke or a traumatic brain injury, to return to their baseline normal physical self. Medical providers like physical therapists or speech therapists often are involved in this therapy process through speech and physical therapy for a specified length of time or until the patient shows improvement and they no longer need therapy. However, the patient with a cognitive dysfunction after an injury cannot reach what was perhaps their normal mental self without cognitive rehabilitation therapy (CRT). For some, the normal they seek to return to is beyond the realm of traditional therapy and simply a physical deficit. That is where CRT can benefit patients in their rehabilitation process with disabilities in their cognitive function, which are not as obvious to others, like a limp or a slurred speech.